Improved electrochemical performance of LiMn1.5M0.5O4 (M=Ni, Co, Cu) based cathodes for lithium-ion batteries - Gonçalves, Renato Ferreira (2021)
LiMn2O4 and LiMn1.5M0.5O4 (M: Ni, Cu, Co) doped particles have been synthetized by sol-gel. Particles between 50 and 200 nm were obtained with the cubic spinel structure of the LiMn2O4. Ni doping shows a more efficient substitution in the octahedral 16d site, replacing the Mn3+ thorn ion, improving the important drawback of poor cycling behavior of LiMn2O4. The average pore size decrease with the addition of the doped elements in the LiMn2O4 structure from 2.9 to 2.6 nm. Thermal analysis shows that the doped particles present higher thermal stability that the undoped ones. Electrochemical behavior of the cathodes prepared with each of the active materials show that the doping influenced the electrochemical performance of the active material. Thus, a specific capacity of 33, 74, 44 and 53 mAh g(-1) (at C) and 74, 89, 59 and 69 mAh g(-1) (at C/10) were obtained for LiMn2O4, LiMn1.5Ni0.5O4, LiMn1.5Cu0.5O4 and LiMn1.5Co0.5O4 cathodes, respectively. All cathodes present good electrochemical stability with low capacity fade of 0.5 and 3.1% for LiMn1.5Ni0.5O4 and LiMn1.5Cu0.5O4, respectively, after 50 cycles. These results show an improvement of electrochemical performance for LiMn2O4 doped with Ni, Cu and Co, demonstrating their suitability for lithium-ion battery systems.